Implications of climate change for the reproductive capacity and survival of New World silversides (family Atherinopsidae) - Strüssmann, C. A. (2010)
The New World silversides (family Atherinopsidae) are found in marine, estuarine and inland waters of North, Central and South America, where they are ecologically important as forage fishes and sometimes economically important for commercial and recreational fisheries. This report reviews the knowledge of the reproductive attributes of temperate and subtropical atherinopsids in relation to temperature and discusses the potential effects of climate change on their reproduction and adaptive responses. Their reproductive cycles are primarily entrained by photoperiod with high temperature acting as a limiting factor. They are generally multiple spawners which release successive batches of eggs in spring, but some species can spawn also in autumn and even summer when temperatures do not increase excessively. The decoupling of temperature patterns and photoperiod with further global warming and associated asymmetric thermal fluctuations could lead to spawning at times or temperatures that are unsuitable for larval development and growth. Many members of this family show temperature-dependent sex determination (TSD), where the phenotypic sex of an individual is determined partly or wholly by the temperature experienced during gonadal sex differentiation, and high-temperature induced germ cell degeneration and decreased fertility. The predicted short-term reproductive responses of atherinopsids to climate change therefore include acceleration, shortening or overall disruption of spawning activity, and also more subtle, but nonetheless equally population-threatening, dysfunctions such as highly skewed sex ratios and partial or total loss of fertility. In the case of species with TSD, asymmetric thermal fluctuations could also cause larvae to encounter temperatures lower than normal during early development and be feminized. Such dysfunctions have been documented already in natural populations but are confined so far to landlocked, inland water habitats, perhaps because they impose more severe thermal fluctuations and limitations to migration and dispersal. The severity and recurrence of these dysfunctions with further climate change will depend both on the magnitude, speed and pattern of change and on how much (or how fast) physiological and behavioural traits can evolve to match the new conditions imposed by the climate, which is largely unknown. In this regard, compelling evidence is shown that numerous traits, including the sex determination system, are capable of rapid evolution and could mitigate the negative effects of temperature increases on population viability in atherinopsids.